(Re)conceptualisation of ELT professionals: academic high school English teachers' professional identity in Korea. Issue 5 (3rd July 2016) - Han, Insuk
Abstract: This study investigates Korean English teachers' responses to the current English Language Teaching (ELT) policies and reveals the attributes of their professional identity from their responses. Data collected from different narratives demonstrate that the teachers value the principles of communicative language teaching, but are not supportive of teaching English in English and do not regard oral competence as a prerequisite for ELT professionals, both of which are the main concern of the current policies. The teachers emphasise human education, having practical knowledge and willingness to learn something new, and using different methods or materials depending on the students' needs and levels. These understandings of the meaning systems of their professional identity provide some implications for the establishment of professional standards and desirable pedagogies, as well as the reform of the English curriculum. First, broader attributes of the teachers' qualities need to be reflected into professional standards. Second, the state needs to form a partnership with the teachers that leads to producing a more feasible and coherent curriculum. Third, to be accredited as professionals, English teachers' active reflection on their own teaching is indispensable.